2015
DOI: 10.1149/2.0711514jes
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Low Voltage Behavior of V2O5Aerogel as Intercalation Host for Sodium Ion Battery

Abstract: Boosted by costs benefits, the development of room temperature Na-ion batteries is strongly desired for stationary applications. In this study we explore the possible use of V 2 O 5 aerogel as anode material for sodium ion batteries. The aerogel is able to reversibly insert more than 3 Eq. of sodium in the voltage range 0.1 V-4 V vs. Na/Na + demonstrating to possess additional capacity when cycled to lower voltage. The anode delivers about 200 mAh g −1 in the voltage range 0.01 V-1.5 V vs. Na/Na + . The prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 57 publications
(82 reference statements)
6
68
2
Order By: Relevance
“…[141][142][143] The rate capabilities are satisfactory, [111,139,144] but the long term cycling ability has been not yet assessed as generally not more than 100 cycles are reported and the cyclability is very much linked with the sample morphology and electrode preparation. [148] However, the possible use of this material as anode for Na-ion batteries is hindered by the need of an effective preliminary sodiation treatment to account for the large irreversible capacity loss during the first cycle. Tapavcevic et al [60] reported the reversible expansion of interlayer distance and increase of the bond lengths within the bilayers upon Na + (de-)insertion process in agreement with the findings of Su.…”
Section: Sodiummentioning
confidence: 99%
“…[141][142][143] The rate capabilities are satisfactory, [111,139,144] but the long term cycling ability has been not yet assessed as generally not more than 100 cycles are reported and the cyclability is very much linked with the sample morphology and electrode preparation. [148] However, the possible use of this material as anode for Na-ion batteries is hindered by the need of an effective preliminary sodiation treatment to account for the large irreversible capacity loss during the first cycle. Tapavcevic et al [60] reported the reversible expansion of interlayer distance and increase of the bond lengths within the bilayers upon Na + (de-)insertion process in agreement with the findings of Su.…”
Section: Sodiummentioning
confidence: 99%
“…A VO 2 ·1.65H 2 O/graphene composite was shown to deliver a reversible capacity of ≈210 mA h g −1 between 2.5-0.05 V versus Na +/ Na at 10 mA g −1 and after 20 cycles, although with rather low coulombic efficiency (≈67% after 20 cycles). [149] NaZr 2 (PO 4 ) 3 also crystallizes in the NASICON structure and can accommodate extra Na ions, delivering a capacity of 150 mA h g −1 at 20 mA g −1 between 2.5 and 0.01 V. It is proposed that the reaction occurs through the reduction of Zr +4 to Zr +2 , as concluded from XPS data, [150] although Zr +2 is quite rare and XPS peak assignment would be compatible with a reduction to Zr +3 . [148] V 2 O 5 was shown to deliver ≈250 mA h g −1 at C/2 in the voltage range of 2-0.01 V when prepared as an aerogel.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[273] The reported battery showed an operation voltage of 1.8 V and good rate capabilities with 70% of the original capacity retained at 11 C. Moreover, Yang and co-workers built a double-wall Sb@TiO 2−x structure [274] by the calcination of Sb 2 S 3 @TiO 2 nanorods, in a Ar/H 2 atmosphere, produced by the hydrolysis of tetrabutyl titanate on Sb 2 S 3 nanorods. [276] When evaluated as Na 3 V 2 (PO 4 ) 3 //V 2 O 5 , the full-cell displays the capacities of 113 and 60 mAh g −1 based on the anode and cathode materials, respectively. In this compound the excellent electrochemical stability of TiO 2−x is combined with the high theoretical capacity of Sb as an alloying material.…”
Section: Transition Metal Oxides-based Sibs Full-cellsmentioning
confidence: 99%